Wayang Image Classification Using MLP Method and GLCM Feature Extraction - M. Hamdani Santoso; Diah Ayu Larasati; Muhathir Muhathir (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2020)
Wayang is a form of shadow art that has been known to the Javanese people more than 1500 years ago. For Javanese people, the function of wayang is not only as a spectacle but also as a request, because in the wayang story there are values that are important to Javanese society. Wayang has developed from time to time, there are many types of wayang in Indonesia, with many types of wayang in Indonesia, of course preserving the art of wayang kulit is not an easy thing, especially because this traditional art is not yet very popular among young people, especially in the regionsburban. Today's young people use technology more in finding information, such as using laptops or smartphones. Because to make it easier for people who want to know about puppets and their types, a technology is created that can distinguish the types of puppets based on wayang images. So this research was made using the MLP (The Multi Layer Perceptron) method and its extraction feature GLCM (Gray-Level Co-Occurrence Matrix) with a total system accuracy of recognizing wayang image objects up to 73.4%.